2019
DOI: 10.1186/s12879-019-3982-7
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of factors associated with detection of oncogenic human papillomavirus in human immunodeficiency virus-infected and uninfected Kenyan women

Abstract: Background: Cervical cancer is caused by oncogenic human papillomaviruses (HPV) and is one of the most common malignancies in women living in sub-Saharan Africa. Women infected with the human immunodeficiency virus (HIV) have a higher incidence of cervical cancer, but the full impact on HPV detection is not well understood, and associations of biological and behavioral factors with oncogenic HPV detection have not been fully examined. Therefore, a study was initiated to investigate factors that are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…However, these data suggest that HIV‐infected women infected with HR‐HPV may be more likely to present with more advanced cervical lesions compared to HIV‐uninfected women, which is consistent with previous research 8,17 . These findings also echo previous research demonstrating increased risk of HPV infection among women infected with HIV in spite of ART usage 14,15,18–22 . The literature further explains the finding that HIV‐infected women were more likely to have types of LR‐HPV identified compared to HIV‐uninfected women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, these data suggest that HIV‐infected women infected with HR‐HPV may be more likely to present with more advanced cervical lesions compared to HIV‐uninfected women, which is consistent with previous research 8,17 . These findings also echo previous research demonstrating increased risk of HPV infection among women infected with HIV in spite of ART usage 14,15,18–22 . The literature further explains the finding that HIV‐infected women were more likely to have types of LR‐HPV identified compared to HIV‐uninfected women.…”
Section: Discussionsupporting
confidence: 89%
“…For HIV‐infected women, variables were collected from the AMPATH Medical Record System (AMRS) at enrollment including date of diagnosis of HIV, use of antiretroviral therapy (ART), HIV viral load, and CD4 count. This questionnaire was the same used in Ermel et al 15 in 2019 in a different cohort of women.…”
Section: Methodsmentioning
confidence: 99%
“…Two-third of HPV68 was associated with multiple infections and its frequency was more than 2 times higher in HIV infected women. This is consistent with another study in the same region of Kenya where a high HPV68 prevalence among HIV-infected women was found 33 . A study conducted in an isolated rural community in Brazil reported HPV68 as the most prevalent genotype, however it was not present in women with cytological abnormalities 45 .…”
Section: Hpv Genotypessupporting
confidence: 93%
“…We found a high overall burden (32.5%) of high-risk HPV infections in our study population, similar to results from another study in our Western Kenya region 33 . A number of other studies done in SSA report lower 34 35 36 37 38 39 or similarly high 40 41 HPV burden.…”
Section: Hpv Burdensupporting
confidence: 91%
“…Two-third of HPV68 was associated with multiple infections and its frequency was more than 2 times higher in HIV infected women. This is consistent with another study in the same region of Kenya where a high HPV68 prevalence among HIV-infected women was found [34]. A study conducted in an isolated rural community in Brazil reported HPV68 as the most prevalent genotype, however it was not present in women with cytological abnormalities [45].…”
Section: Hpv Genotypessupporting
confidence: 91%